Effect of absenteeism and staff turnover of the productivity and sale of ecuadorian pork slaughter and sale company: 2020-2021 - Llanos Encalada, Monica; Castillo Corral, Karen Krystel (Estudios de Administración, 2022)
Staff turnover and absenteeism in the company, have increased, causing job dissatisfaction due to factors such as the position held and working conditions. The objective of the research was to analyze the factors that affect productivity, which also influences the dual worker- employer link. The internal rotation of collaborators has been implemented as a solution to cover the absence of others. The methodology used consisted of a qualitative and quantitative approach that allowed analyzing the variables raised, with a descriptive and explanatory cross. Sectional, non- experimental investigation that led to the identification of the causes and dissatisfactions presented by the staff, from the perspective of the worker, they take on a supporting role. Through documentary analysis and application of surveys, the relationship of direct influence that exists between the variables is verified.